Antihypertensive Choices during Pregnancy in Limited Setting - Ernawati, -
Abstract Background: Antihypertensive agents used during pregnancy may vary from institution to institution and depend on resource availability. Objective: This study aimed to determine the profile of antihypertensive drugs used in pregnancy in low-middle-income countries and the impact of these drugs on maternal and fetal outcomes. Materials and Methods: This is a retrospective study on hypertensive pregnant patients admitted to the emergency unit at a tertiary referral Hospital in Indonesia. The type of hypertension during pregnancy, antihypertensive drugs, side effect, and maternal and perinatal outcomes was extracted from medical hospital records. Results: A total of 762 hypertensive pregnant women were recruited; 61 were diagnosed with preeclampsia, 491 were preeclampsia with severe features and 174 were chronic hypertension superimposed preeclampsia, and 81.54% of them received antihypertension therapy. The most commonly prescribed antihypertensive drugs were combination therapy of nifedipine and methyldopa (96.7%), followed by monotherapy of methyldopa (2.3%), nicardipine (1.1%), and nifedipine (0.2%). Most of the patients successfully attained a Systolic blood pressure<160mmHg. Tachycardia was reported in 47 (7.9%) pregnant women who received antihypertensive medication; none reported hypotension and arrhythmia. Conclusion: Nifedipine and methyldopa are choices for an antihypertensive agent in limited resources, either monotherapy or combined. Nifedipine's immediate release can be used with a low risk of hypotension.